Self-driven ultraviolet light detector based on Mxene-AlInGaN heterojunction and preparation method thereof

By using the combination of Mxene-AlInGaN heterojunction and flexible backplane in the UV detector, the existing UV detectors are solved, and the zero-biased self-drive function and efficient light collection capabilities are achieved, which are suitable for the needs of the modern microelectronics industry.

CN115692538BActive Publication Date: 2025-03-28NANJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211400883.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-09
Publication Date
2025-03-28
Estimated Expiration
2042-11-09

AI Technical Summary

Technical Problem

Existing ultraviolet detectors have problems such as large volume, high working voltage, and fragility. Silicon-based ultraviolet devices have deteriorated performance due to narrow band gap and high temperature diffusion, making it difficult to meet the needs of the modern microelectronics industry.

Method used

Using a self-driven ultraviolet detector based on the heterogeneous integration of Mxene thin layer and AlInGaN semiconductor, the heterocarrier is transferred to the flexible backplane through laser peeling method to achieve the zero-biased self-drive function, and the light collection and current expansion capabilities are improved through the high light transmittance of Mxene thin layer and the high conductivity of AlInGaN.

Benefits of technology

It realizes the self-drive output photocurrent under zero bias, improves the device's working efficiency and light collection ability, reduces manufacturing costs, and expands the device's application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115692538B_ABST
    Figure CN115692538B_ABST
Patent Text Reader

Abstract

The present invention discloses a self-driven ultraviolet light detector based on Mxene-aluminum-indium-gallium-nitrogen heterojunction and a preparation method thereof, wherein the substrate material is an AlInGaN semiconductor epitaxially grown on a sapphire substrate, and the surfaces of the detector are respectively a metal electrode, an Mxene thin layer and a test electrode, wherein Mxene and AlInGaN form a heterojunction. The work function difference between Mxene and AlInGaN generates a Schottky barrier at the heterojunction interface, which can separate photogenerated electron / hole pairs under zero bias and output photocurrent, that is, the detector has a self-driving function. The Mxene thin layer has good ultraviolet light transmittance and can expand the photosensitive area of ​​the device. At the same time, the negative electrode of the detector forms an ohmic contact with AlInGaN after annealing, which can quickly collect electrons and improve the working efficiency of the detector. The present invention also provides a laser lift-off transfer method for the Mxene-AlInGaN heterojunction, which can further produce a flexible self-driven ultraviolet light detector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoelectric detectors, and in particular relates to a self-driven ultraviolet light detector based on heterogeneous integration of a Mxene thin layer and an AlInGaN semiconductor and a preparation method thereof. Background Art

[0002] As a basic photoelectric element, ultraviolet detectors can convert incident short-wavelength (<400nm) radiation into electrical signals for further processing. They are widely used in communications, imaging, biological detection, chemical analysis, and daily monitoring. At present, commercial ultraviolet detectors are mainly based on vacuum photomultiplier tubes and ultraviolet-enhanced silicon-based photodiodes. When vacuum devices use vacuum tubes, their large size, high operating voltage, and fragility increase the manufacturing cost of the device. Silicon-based ultraviolet devices are not conducive to the absorption of ultraviolet light due to the narrow band gap of silicon, and the indirect band gap will reduce the quantum efficiency of the device. In addition, the preparation of high-performance silicon-based photodiodes is also limited by micromachining processes. For example, high-temperature diffusion and ion implantation usually shorten the minority carrier lifetime, resulting in a significant decrease in device performance.

[0003] In order to meet the requirements of the modern microelectronics industry, UV detectors based on new materials and device structures are still being explored. Two-dimensional layered materials have received extensive attention and research due to their strong light-matter interaction, thickness-dependent band gap, high in-plane carrier mobility, and interlayer van der Waals forces. Among them, Mxene is a new two-dimensional material composed of transition metal carbides or carbonitrides. Mxene colloidal solutions can be made into high-quality Mxene films by simple methods such as drop casting and spin coating. Ultrathin Mxene layers have high transmittance, low resistivity and mechanical flexibility, which are conducive to their application in photoelectric detection and flexible electronic devices. In addition, group III nitride semiconductors are widely used in power devices, light-emitting diodes (LEDs), laser diodes (LDs), photodetectors and other fields, and they occupy a certain position in flexible electronics. Among them, hexagonal wurtzite structure AlInGaN has high thermodynamic, mechanical and chemical stability, and its wide direct band gap of 3.4-5.0eV is suitable for short-wavelength UV detectors.

[0004] This patent invented a self-driven UV detector, which integrates two-dimensional Mxene and three-dimensional AlInGaN. The Schottky barrier at the heterojunction interface enables the detector to output photocurrent at zero bias. The laser lift-off method is used to transfer the heterojunction to a flexible backplane to obtain a flexible UV detector that can be flexibly bent. Thanks to the high light transmittance of the Mxene thin layer and the high conductivity of AlInGaN, the detector exhibits excellent light collection and current expansion capabilities. Summary of the invention

[0005] Purpose of the invention: The present invention provides a self-driven ultraviolet light detector based on Mxene-AlInGaN heterojunction and a preparation method thereof, wherein the detector has a self-driven function under zero bias.

[0006] Technical solution: A self-driven ultraviolet light detector based on Mxene-GaN heterojunction, comprising:

[0007] The substrate is an AlInGaN epitaxial layer wafer, which includes a buffer layer u-AlInGaN, a current spreading layer n-AlInGaN and a non-doped u-AlInGaN layer from bottom to top;

[0008] In a partial area of ​​the substrate, a first area is formed by etching to the current spreading layer, and an unetched area forms a second area;

[0009] A metal negative electrode is located in the first region and is formed by evaporating metal on the surface of the first region;

[0010] A positive electrode, located in the second region, formed by depositing a Mxene material at a predetermined position in the second region;

[0011] Alternatively, the upper surface of the non-doped layer in the substrate is divided into two spaced regions;

[0012] The metal negative electrode and the positive electrode are respectively located in one of the regions, and the positive electrode is formed by depositing the Mxene material at a predetermined position.

[0013] According to one aspect of the present application, a metal test electrode is formed on a side of the positive electrode away from the non-doped u-AlInGaN layer.

[0014] According to one aspect of the present application, in the AlInGaN epitaxial layer wafer, the composition of the AlInGaN material is Al x In y Ga (1-x-y) N; where 0 <x<0.7,0<y<0.3。

[0015] According to one aspect of the present application, the thickness of the n-AlInGaN in the current spreading layer is 0.1-10.0 μm, and the electron concentration is 1*17 cm -3 ~1*20cm -3 ;

[0016] The thickness of the undoped u-AlInGaN is 0.01-1 μm, and the electron concentration is 1*16 cm -3 ~1*17cm -3 .

[0017] According to one aspect of the present application, the thickness of the metal negative electrode is 20-120nm, and the metal used in the metal negative electrode includes Ti, Al, Ni and Au. After annealing, the metal melts into an alloy to form an electrical contact with the current spreading layer.

[0018] According to one aspect of the present application, the thickness of the positive electrode is 5-50 nm, the metal test electrode is formed by evaporating Au, and the thickness of the metal test electrode is 200 nm.

[0019] According to another aspect of the present application, a method for preparing the above-mentioned detector is provided, comprising the following steps:

[0020] Step 1: Cut the substrate into required size, clean the substrate and blow dry it;

[0021] Step 2, soaking the substrate to improve the hydrophilicity of the substrate surface;

[0022] Step 3, etching a portion of the substrate to the current spreading layer to expose the surface of the current spreading layer;

[0023] Step 4: photolithography a negative electrode pattern on the current spreading layer, using electron beam evaporation technology to evaporate metal on the current spreading layer as a negative electrode; using rapid thermal annealing technology to form an alloy under high temperature annealing;

[0024] Step 5, preparing a Mxene colloidal solution, photolithography a positive electrode pattern in an unetched area on the substrate, and coating the Mxene solution on the surface of the unetched area by spray deposition and drying;

[0025] Step 6: Use vacuum annealing technology to perform vacuum thermal annealing on the Mxene thin layer to form a positive electrode.

[0026] According to one aspect of the present application, in step 7, a pattern is formed on a partial surface area of ​​the dried Mxene layer, and metal Au is evaporated using electron beam evaporation technology as a test electrode.

[0027] According to one aspect of the present application, in step 8, a laser lift-off method is used to separate the buffer layer u-AlInGaN from the sapphire substrate, and the detector is transferred to a flexible backplane coated with an adhesive using UV tape to obtain a bendable flexible ultraviolet detector.

[0028] According to one aspect of the present application, the Mxene colloid solution is composed of Ti 3 C 2 Tx particles were dissolved in deionized water and obtained after repeated washing and precipitation by centrifuge.

[0029] Beneficial effects:

[0030] 1. The designed detector has a self-driving function and can output photocurrent under zero bias, which is beneficial to improve the working efficiency of the device. The Mxene thin layer has high light transmittance and can expand the photosensitive area of ​​the non-u-doped AlInGaN photosensitive layer, effectively improving the light collection ability of the detector. The evaporated Ti / Al / Ni / Au forms an ohmic contact with n-AlInGaN, which is beneficial to enhance the current collection ability of the device.

[0031] 2. The present invention utilizes laser stripping and UV tape to transfer the detector to a flexible backplane, thereby achieving flexible bending and strain of the detector and expanding the application scenarios of the device.

[0032] 3. The present invention also provides a simple and efficient Mxene solution spraying process, which can adjust the deposition thickness of the Mxene film by changing the solution concentration or the spraying amount, and this method reduces the manufacturing cost of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the structure of the Mxene-AlInGaN heterojunction self-driven ultraviolet light detector.

[0034] Among them: 1 is a sapphire substrate, 2 is an epitaxially grown buffer layer u-AlInGaN, 3 is a current spreading layer n-AlInGaN, 4 is a non-doped u-AlInGaN, 5 is a vapor-deposited metal Ti / Al / Ni / Au, 6 is a spray-deposited Mxene thin layer, and 7 is a vapor-deposited test electrode Au.

[0035] Figure 2 is the transmittance of the Mxene thin layer.

[0036] Figure 3 Schematic diagram of the structure of the Mxene-AlInGaN heterojunction self-driven ultraviolet light detector transferred to a flexible backplane.

[0037] Among them: 8 is a Mxene-AlInGaN self-driven ultraviolet light detector, 9 is a flexible backplane, including copper foil, PET

[0038] Plastic and flexible glass, etc.

[0039] Figure 4 These are the current-voltage curves of the detector output under no illumination, 365nm illumination, and 254nm illumination after it was transferred to the curved flexible backplane. Specific implementation methods

[0040] In order to introduce the present invention more clearly, the specific implementation method of the present invention will be described below with reference to examples.

[0041] A self-driven ultraviolet light detector based on Mxene-AlInGaN heterojunction uses u-AlInGaN as a photosensitive layer. The Mxene solution is sprayed on the surface of u-AlInGaN by a spray deposition method. After drying and annealing, the Mxene forms a thin film that acts as a transparent positive electrode. The transparent electrode can increase the light-receiving area of ​​the photosensitive layer.

[0042] The substrate is an AlInGaN epitaxial layer wafer, which is grown epitaxially on a sapphire substrate using metal-organic chemical vapor deposition. The structure of AlInGaN from bottom to top is the buffer layer u-AlInGaN, the current spreading layer n-AlInGaN and the undoped u-AlInGaN. The current spreading layer composed of electron-doped n-AlInGaN has high conductivity and is more likely to form ohmic contact with the negative electrode metal, which is conducive to the negative electrode to quickly collect electrons and increase the output current value, thereby improving the response speed and light response of the detector.

[0043] In addition, the MXene film consists of a few layers of Ti 3 C 2 Composed of Tx material, the thickness of the Mxene film is 5~50nm, and the transmittance near the 365nm band is as high as 73%.

[0044] Preferably, a negative electrode Ti / Al / Ni / Au is evaporated on the n-AlInGaN surface of the ultraviolet detector with a thickness of 20 / 120 / 50 / 100 nm, and a test electrode Au is evaporated on the Mxene surface with a thickness of 200 nm.

[0045] It can be transferred to a flexible backplane via laser peeling, and the flexible backplane includes copper foil, PET plastic, and flexible glass.

[0046] A method for preparing a self-driven ultraviolet light detector based on a Mxene-AlInGaN heterojunction, the steps comprising:

[0047] (1) Cut the AlInGaN substrate into the required size, clean the substrate and blow dry it.

[0048] (2) Soak the AlInGaN substrate in piranha solution to make the substrate surface hydrophilic.

[0049] (3) Etch part of the AlInGaN area to the current spreading layer to expose the n-AlInGaN.

[0050] (4) Photolithography of the negative electrode pattern is performed on n-AlInGaN, and electron beam evaporation technology is used to evaporate metal Ti / Al / Ni / Au on the surface of n-AlInGaN as the negative electrode.

[0051] (5) Rapid thermal annealing technology is used to form an alloy of Ti / Al / Ni / Au under high temperature annealing.

[0052] (6) Preparation of Mxene colloidal solution,

[0053] (7) Photolithography of the positive electrode pattern in the unetched area, coating the Mxene solution on the non-doped u-AlInGaN surface by spray deposition and drying.

[0054] (8) Using vacuum annealing technology, vacuum thermal annealing is performed on the Mxene thin layer.

[0055] (9) Photolithography was performed on some areas of the Mxene surface, and metal Au was evaporated using electron beam evaporation technology as a test electrode.

[0056] (10) The buffer layer u-AlInGaN was separated from the sapphire substrate by laser lift-off method, and the detector was transferred to a flexible backplane coated with adhesive using UV tape to obtain a bendable flexible UV detector.

[0057] Embodiment 1:

[0058] A self-driven ultraviolet light detector of Mxene-AlInGaN heterojunction, based on the work function difference between Mxene and AlInGaN, will generate Schottky barrier and built-in electric field at the heterojunction interface, which can fully separate photogenerated electron / hole pairs under zero bias. After the photoelectrons pass through the highly doped n-AlInGaN current extension layer, they can be quickly collected by Ti / Al / Ni / Au electrodes and output photocurrent, so that the detector has self-driving function under zero bias. The specific steps are as follows:

[0059] (1) Cut the AlInGaN substrate into 2x2 cm samples and ultrasonically clean the samples with acetone, ethanol, and deionized water for 5 min each.

[0060] (2) Mix concentrated sulfuric acid and 30% hydrogen peroxide solution in a ratio of 3:1 to make a piranha solution. Soak the AlInGaN sample in the piranha solution for 2 minutes to make the sample surface hydrophilic. Then take out the sample, wash the residual piranha solution on the surface with deionized water and blow dry.

[0061] (3) Using ICP process, photoresist is used as etching mask, and Cl 2 and BCl 3 The mixed gas etches part of the AlInGaN area to the n-AlInGaN layer. After the etching is completed, the residual glue on the surface of the sample is cleaned with acetone and ethanol respectively.

[0062] (4) A negative electrode pattern was photolithographically formed on the surface of n-AlInGaN. Using photoresist as a mask, electron beam evaporation technology was used to evaporate metal Ti / Al / Ni / Au (20 / 120 / 50 / 50 nm) on the n-AlInGaN as a negative electrode.

[0063] (5) Thermal annealing treatment is performed using a rapid annealing furnace. The sample is heated to 750°C in a nitrogen atmosphere and maintained at this temperature for 1 min. The Ti / Al / Ni / Au on the n-AlInGaN will melt to form an alloy and form a good ohmic contact with the n-AlInGaN, which is beneficial to improving the current output.

[0064] (6) Use an analytical balance to weigh about 3 grams of Ti 3 C 2 The Tx particles were dissolved in deionized water to obtain a MXene solution. The solution was first washed by a centrifuge (800 rpm, 20 min). After the centrifugation, the surface clear liquid in the solution was poured out, the precipitate was collected, and deionized water was added again to disperse the precipitate. The above centrifugation and washing process was repeated several times to finally obtain a MXene colloidal solution containing a layered structure.

[0065] (7) Photolithography of the positive electrode pattern on the unetched non-doped u-AlInGaN, using the photoresist as a mask, spraying the obtained Mxene colloidal suspension on the u-AlInGaN surface using a spray gun, and depositing the Mxene nano-thin layer by controlling the spray amount of the Mxene solution while maintaining a constant spray flow rate. After spraying, the Mxene-AlInGaN heterojunction sample is moved to a glove box in a nitrogen atmosphere for drying.

[0066] (8) Using vacuum annealing technology, Mxene-AlInGaN is placed in an annealing furnace, the annealing furnace is evacuated and then heated to 200°C and maintained for 150 minutes to obtain a high-quality Mxene thin layer. At the same time, Mxene will form a good interface contact with u-AlInGaN.

[0067] (9) Photolithography patterns were formed on a part of the surface of Mxene, and electron beam evaporation technology was used to evaporate metal Au (200 nm) on Mxene as a test electrode using photoresist as a mask.

[0068] (10) Using the laser lift-off method, the KrF excimer laser is irradiated on the sapphire substrate at the bottom of the device for about 0.1 seconds, which can etch away part of the u-AlInGaN at the interface between the sapphire and the device. The detector is adhered to the sapphire with UV tape and peeled off from the sapphire to complete the lift-off. The adhesive is spin-coated on the flexible backplane, and the peeled detector and the UV tape are transferred to the flexible backplane with adhesive. Then, the UV light is used to irradiate for 10 minutes to make the UV tape lose its adhesiveness and fall off.

[0069] At this point, the UV detector of this patent invention has been completed. The flexibility and deformation of the detector can be achieved by bending the back plate. Probes were inserted into the Au electrode and Ti / Al / Ni / Au electrode for testing. UV light (200~400nm) was irradiated on the detector sample. It was found that the device can also output photocurrent under zero bias. Compared with the dark current, the photocurrent gain can reach 10 4 .

[0070] Embodiment 2:

[0071] A self-driven ultraviolet light detector of Mxene-AlInGaN heterojunction, which is different from Example 1 in that the Mxene thin layer and Ti / Al / Ni / Au on the detector are both located on the surface of non-doped u-AlInGaN, that is, the ICP process is not used, the complete AlInGaN substrate is retained, and Mxene and Ti / Al / Ni / Au are directly plated on different areas of the u-AlInGaN on the substrate surface. Due to the lower electron concentration and mobility of u-AlInGaN, the dark current of the detector will be further reduced at this time, and when ultraviolet light is irradiated to the detector surface, the output photocurrent gain will be increased, so that the device has a higher ultraviolet light detection signal-to-noise ratio.

Claims

1. A self-driven ultraviolet light detector based on Mxene-GaN heterojunction, characterized in that: include: The substrate is an AlInGaN epitaxial layer wafer, which includes a buffer layer u-AlInGaN, a current spreading layer n-AlInGaN and a non-doped u-AlInGaN layer from bottom to top; In a partial area of ​​the substrate, a first area is formed by etching to the current spreading layer, and an unetched area forms a second area; A metal negative electrode is located in the first region and is formed by evaporating metal on the surface of the first region; A positive electrode, located in the second region, formed by depositing a Mxene material at a predetermined position in the second region; The thickness of n-AlInGaN in the current spreading layer is 0.1-10.0 μm, and the electron concentration is 1*17 cm -3 ~1*20cm -3 ; The thickness of the undoped u-AlInGaN is 0.01-1 μm, and the electron concentration is 1*16 cm -3 ~1*17cm -3 ; In the AlInGaN epitaxial layer wafer, the components of the AlInGaN material are Al x In y Ga (1-x-y) N; where 0 <x<0.7,0<y<0.3; The buffer layer u-AlInGaN was separated from the sapphire substrate by laser lift-off, and the detector was transferred to a flexible backplane coated with adhesive using UV tape.

2. The detector according to claim 1, characterized in that A metal test electrode is formed on a side of the positive electrode away from the non-doped u-AlInGaN layer.

3. The detector according to claim 1, characterized in that The thickness of the metal negative electrode is 20-120 nm. The metals used in the metal negative electrode include Ti, Al, Ni and Au. After annealing, the metals are melted into alloys to form electrical contact with the current expansion layer.

4. The detector according to claim 2, characterized in that The thickness of the positive electrode is 5-50 nm, and the metal test electrode is formed by evaporating Au, and the thickness of the metal test electrode is 200 nm.

5. A method for preparing the detector according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Cut the substrate into required size, clean the substrate and blow dry it; Step 2, soaking the substrate to improve the hydrophilicity of the substrate surface; Step 3, etching a portion of the substrate to the current spreading layer to expose the surface of the current spreading layer; Step 4: photolithography a negative electrode pattern on the current spreading layer, using electron beam evaporation technology to evaporate metal on the current spreading layer as a negative electrode; using rapid thermal annealing technology to form an alloy under high temperature annealing; Step 5, preparing a MXene colloidal solution, photolithography a positive electrode pattern in an unetched area on the substrate, and coating the MXene solution on the surface of the unetched area by spray deposition and drying; Step 6: Use vacuum annealing technology to perform vacuum thermal annealing on the Mxene thin layer to form a positive electrode.

6. The method according to claim 5, characterized in that Also includes: Step 7: Photolithography patterns are formed on a part of the surface of the dried Mxene layer, and metal Au is evaporated using electron beam evaporation technology as a test electrode.

7. The method according to claim 6, characterized in that Also includes: Step 8: Use laser lift-off method to separate the buffer layer u-AlInGaN from the sapphire substrate, and use UV tape to transfer the detector to a flexible backplane coated with adhesive to obtain a bendable flexible ultraviolet detector.

8. The method according to claim 5, characterized in that The Mxene colloidal solution is obtained by dissolving Ti3C2Tx particles in deionized water and repeatedly washing and precipitating them in a centrifuge.

Citation Information

Patent Citations

  • PIN structure ultraviolet photoelectric detector and preparation method thereof

    CN108574020A

  • Photoelectric detector and manufacturing method thereof

    CN114005895A